TINJAUAN TERHADAP PUTUSAN HAKIM DI PENGADILAN AGAMA MUARA ENIM KELAS 1B DALAM PERKARA WANPRESTASI AKAD PEMBIAYAAN MURABAHAH OLEH PENGGADAI KEBUN TERHADAP PT. BNI SYARIAH KANTOR CABANG PRABUMULIH - Ramadhania, Ine Chintya; Kencana, Ulya; Lubis, Ramiah (Program Studi Muamalah Fakultas Syariah dan Hukum, 2019)
This thesis is entitled Judge Decision in the Muara Enim Religious Court in the case of a default of murabahah financing contract by the pawnbroker of the BNI Syariah Branch Office Prabumulih with the background of the problem in the murabahah financing contract especially the problems that arise in the contract, one of which is default. Like what often happens in people's lives now. Most people choose the way to borrow money from existing banks so that the existence of Sharia Banking with its range of products is expected to accommodate the interests of the community (customers) who want the banking system to use Sharia principles because Indonesian people are interested in Banking, Financial, Commercial activities and Investment in accordance with the Shariah rules. The problem raised in this thesis is to find out whether the legal issues between BNI Syariah Banking in the form of default and to know the legal reasons of the Estuary Enim Religious Court judges in deciding default cases by garden pledge against BNI Syariah in the perspective of sharia economic law. The method used in this study uses a type of qualitative data, the source of data taken from this study is secondary and primary data. Secondary data relating to research subjects obtained from books, internet and legal dictionaries related to this research. The primary data is data taken directly from the research site. Based on the results of the discussion it can be concluded that the default according to the murabahah financing agreement in this case is as stated in the provisions of Article 14 Chapter Promise Injury Events (defaults) arising from the customer not fulfilling the obligations set out in this contract. While the judge's decision is a case in the field of Sharia Banking, with the main object being used as a legal source in adjudicating this case is a murabahah financing contrac.